2013
DOI: 10.5935/abc.20130208
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Computed Tomography Angiography in the Assessment of Acute Chest Pain in the Emergency Room

Abstract: The coronary computed tomography angiography has recently emerged as an accurate diagnostic tool in the evaluation of coronary artery disease, providing diagnostic and prognostic data that correlate directly with the data provided by invasive coronary angiography. The association of recent technological developments has allowed improved temporal resolution and better spatial coverage of the cardiac volume with significant reduction in radiation dose, and with the crucial need for more effective protocols of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…The article by Duarte 66 , published in 2010, clearly demonstrates the growth of computed tomography and its impact on the detection of coronary artery disease. Over the past decade, we observed an increasing number of review articles 67 - 75 and original articles 47 , 52 , 76 - 90 , which reinforces the impact of tomography and magnetic resonance in current cardiovascular imaging.…”
Section: Impact Of the Latest Publications In The Arquivos supporting
confidence: 52%
See 1 more Smart Citation
“…The article by Duarte 66 , published in 2010, clearly demonstrates the growth of computed tomography and its impact on the detection of coronary artery disease. Over the past decade, we observed an increasing number of review articles 67 - 75 and original articles 47 , 52 , 76 - 90 , which reinforces the impact of tomography and magnetic resonance in current cardiovascular imaging.…”
Section: Impact Of the Latest Publications In The Arquivos supporting
confidence: 52%
“…Epidemiological impact – The studies by Bittencourt et al 45 , 46 demonstrated the prognostic potential of computed tomography in symptomatic patients with nonobstructive and obstructive coronary disease. However, Prazeres et al 47 were able to summarize in an unique way the potential of the technique for use in the emergency room, with potential of cost reduction for low-probability patients.…”
Section: Worldwide Impact Of the Latest Publications By Braziliansmentioning
confidence: 99%
“…Another study suggests acute chest pain evaluation with more objective methods, such as coronary angiotomography, for example. Based on the literature, authors have gathered consistent data on the use of such technique, which was more effective, of low cost and allowed the improvement of treatments in the emergency room, as well as decreasing patients' hospitalization time 19 . International studies have looked for a faster and more effective evaluation of acute chest pain by means of biochemical parameters and risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this technique provides relevant data regarding coronary anatomy, calcium scoring, coronary lumen and coronary plaque characteristics, via a noninvasive route. 1 CCTA is frequently used in the emergency room (ER), being a reliable procedure that allows the clinician to safely discharge the patients with suspected acute coronary syndrome and no coronary artery stenosis. 2,3 Despite of many developments in the diagnosis and treatment of this devastating disease, acute coronary syndrome (ACS) remains a major cause of mortality worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In patients presenting to the ER with acute chest pain and evaluated at low-to-intermediate risk for ACS, CCTA can offer relevant details regarding the pa-tient's condition. 8 A negative scan could help the physician to safely discharge the patients who were admitted to the ER for chest pain, without exposing the patient to an unnecessary invasive evaluation. Available data has shown that CCTA has also a high predictive value for favorable outcomes at 1-year follow-up.…”
Section: Introductionmentioning
confidence: 99%